Transcatheter arterial embolization of cystic artery bleeding - Kim, Hyo-Cheol; Jeong, Yun Soo; Han, Kichang; Kim, Gyoung Min (Frontiers in Surgery, 2023)
Purpose The purpose of this study is to assess the safety and clinical outcomes of transcatheter arterial embolization (TAE) via the cystic artery for treating patients with bleeding from the cystic artery. Materials and Methods This retrospective study included 20 patients who underwent TAE via the cystic artery between January 2010 and May 2022. Radiological images and clinical data were reviewed to evaluate causes of bleeding, procedure-related complications, and clinical outcomes. Technical success was defined as the disappearance of contrast media extravasation or pseudoaneurysm, as demonstrated on completion angiography. Clinical success was defined as discharge from the hospital without any bleeding-related issues. Results Hemorrhagic cholecystitis (n = 10) was the most common cause of bleeding, followed by iatrogenic (n = 4), duodenal ulcer (n = 3), tumor (n = 2), and trauma (n = 1). Technical success was achieved in all cases, and clinical success was achieved in 70% (n = 14) of patients. Three patients developed ischemic cholecystitis as a complication. Six patients with clinical failure died within 45 days after embolization. Conclusion TAE through the cystic artery has a high technical success rate in treating cystic artery bleeding, but clinical failure remains a common occurrence due to concurrent medical conditions and the development of ischemic cholecystitis.